Contribution to the knowledge of Lanta Hebard, 1921, with remarks on some male genital characters (Blattaria, Ectobiidae) - Valverde, Alejandra C.; Crespo, Francisco A.; Iglesias, Mónica S. (Zootaxa, 2016)
The genus Lanta Hebard 1921 includes three species found in the Neotropical region. Two species are known from Argentina, L. peniculiger (province of Santa Fe), and L. scotia (provinces of Córdoba and Santiago del Estero) (see Crespo et al. 2010), and one from Brazil, L. borgesae, (Araras, São Paulo) (Rocha e Silva & Vasconcellos, 1984). All species have been described on the basis of male external characters, such as wing veins, leg spines, hypandrium, shape and position of the styli, in addition to coloration and size. Except for a partial representation of the male genitalia of L. borgesae (Rocha e Silva & Vasconcellos 1984), this structure went untreated in morphological and phylogenetic investigations of the Blattaria (Snodgrass 1937; McKittrick 1964; Grandcolas 1996; Klass 1997; Roth 2003;). Females remain unknown.